229k views
3 votes

(3)/(4)(m+n)-(1)/(4)(m-n);m=(1)/(2),n=(1)/(3)

User Runway
by
5.4k points

1 Answer

2 votes

Answer:


(3)/(4)(m+n)-(1)/(4)(m-n) = (14)/(24)

Explanation:

Given


(3)/(4)(m+n)-(1)/(4)(m-n);m=(1)/(2),n=(1)/(3)

Required

Solve

To do this, we simply substitute values of m and n in the given expression


(3)/(4)((1)/(2)+(1)/(3))-(1)/(4)((1)/(2)-(1)/(3))

Evaluate the brackets


(3)/(4)((3 + 2)/(6))-(1)/(4)((3-2)/(6))


(3)/(4)((5)/(6))-(1)/(4)((1)/(6))

Open Brackets


(15)/(24) - (1)/(24)

Take LCM


(15 - 1)/(24)


(14)/(24)

Hence:


(3)/(4)(m+n)-(1)/(4)(m-n) = (14)/(24)

User Oleksiy
by
5.1k points